BAK regulates catalase release from peroxisomes - Yukio Fujiki; Non Miyata; Satoru Mukai; Kanji Okumoto; Emily H. Cheng (Molecular & Cellular Oncology, 2017)
Loss of voltage-dependent anion channel 2 (VDAC2) leads to impaired peroxisome biogenesis in mammalian cells. Knockdown of BAK restores peroxisomal biogenesis in VDAC2-deficient cells, where BAK localization shifts from mitochondria to peroxisomes. Moreover, overexpression of BAK activators in wild-type cells permeabilizes peroxisomes in a BAK-dependent manner. Together, BAK most likely regulates peroxisomal membrane permeability.